Machine learning-driven discovery of novel therapeutic targets in diabetic foot ulcers - Xin Yu; Zhuo Wu; Nan Zhang (BMC, 2024)
Highlights 1. This is the first report identifying SCUBE1 and RNF103-CHMP3 as therapeutic targets for diabetic foot ulcers (DFU). 2. Our study found that SCUBE1 and RNF103-CHMP3 were significantly downregulated in patients who were cured of DFU. 3. This study discovered that SCUBE1 and RNF103-CHMP3 are associated with extracellular interactions. 4. Our findings indicate that SCUBE1 and RNF103-CHMP3 are related to immune cell infiltration. 5. This study provides new theoretical foundations and molecular targets for the diagnosis and treatment of DFU.